Digital Marketing: Competitive Superior Strategy in the Industrial Revolution 4.0 - Erni Widiastuti; Arya Surendra (Institute of Computer Science (IOCS), 2020)
The development of technology and information in the era of the industrial revolution 4.0 has integrated the use of the internet in the production sector in the industrial world. This study aims to analyze the implementation of digital marketing as a competitive superior strategy in the era of the Industrial Revolution 4.0. This research was conducted with a desciptive qualitative design. Data retrieval was carried out by researchers through interview with online shoper in Surakarta and literature studies. The results show that the industrial revolution 4.0 provides a big challenge for the business world to survive in the midst of very competitive competition. Companies that have a competitive advantage are very dependent on the success of their marketing strategies. Digital marketing is a strategy in increasing sustainable competitiveness in the era of the 4.0 industrial revolution, which is carried out by preparing a business identity, introducing business, optimizing social media functions, increasing interaction activities with consumers and expanding reach through broadcast messages containing quality content. Based on this, companies must have an orientation to seize the market in the dynamics of business competition with product advantages that are unique in terms of character so that they are easily recognized and remembered by consumers and have specialization in the eyes of consumers.